PENGARUH TOTAL QUALITY MANAGEMENT DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL PT SAI SURAU GADING KABUPATEN ROKAN HULU - Yogi Adam; Seprini (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of total quality management and reward systems on the managerial performance of PT SAI Surau Gading, Rokan Hulu Regency. The population and sample of this study were all 96 employees of PT SAI Surau Gading, Rokan Hulu Regency. The sampling method uses the census method or saturated sampling. The independent variables in this study are total quality management (X1), reward system (X2) and managerial performance dependent variable (Y). Data collection methods consist of observation, questionnaire and documentation. The analysis technique used is multiple linear regression analysis using the SPSS program. The results of multiple linear regression analysis obtained regression equation Y = 5.642 + 0.154 X1 + 1,203 X2 + e. Partially, a total quality management of 1,388 and an award system of 11,084 were obtained. Simultaneously, an F-count of 491,727 obtained showed that the total quality management and reward system had the same effect on managerial performance. The results showed that 91.4% of managerial performance was influenced by the total quality management and reward system, while the remaining 8.6% was influenced by other variables not examined in this study. The conclusion of this study in partial testing (test) only reward system variables that affect managerial performance while in testing simultaneously (F test) total quality management and reward systems together affect managerial performance.